PERSEPSI MASYARAKAT TERHADAP PENGELOLAAN EKOSISTEM MANGROVE PADA WILAYAH PESISIR DI DESA AKUNI, KECAMATAN TINANGGEA, KABUPATEN KONAWE SELATAN - Gandri, La; Muhsimin, Muhsimin (Universitas Halu Oleo, 2020)
The development of coastal areas continues to grow rapidly in line with the fairly high population growth rate. This study aims to determine the level of community perceptions of mangrove ecosystem management in the coastal area of Akuni Village. The method used is descriptive qualitative analysis to explain the actual conditions at the research location through surveys and in-depth interviews of 10 assessment indicators. The results showed that the level of community perception towards mangrove ecosystem management on the coast of Akuni Village was in the high category. The relatively low socio-economic conditions of the community are not an obstacle in managing mangrove management in Akuni Village in the future because a good understanding of coastal resources, especially mangrove ecosystems, is increasing along with the understanding and actualization of the direct and indirect benefits felt by coastal communities in several the last decade.